APPLICATION OF GAME METHODS AS A BASIS FORMATION OF POSITIVE MOTIVATION NON-LINGUAL UNIVERSITY STUDENTS - Khafizova Mashkhura Aminovna (Web of Journals Publishing, 2024)
The purpose of this article is to study and research methods and forms of using gaming technologies in mastering the Russian language, especially in non-linguistic higher education institutions. The methodology of the article is based on the effective use of various modern pedagogical approaches, accompanied by gaming technologies, when learning Russian as a foreign language.Results: Based on the synthesis and analysis of the motivational components and properties of cognitive games used in teaching Russian in non-linguistic universities, the main tasks and problems of activating the cognitive activity of students and improving the methods of teaching the Russian language were identified and considered. The practical significance of the article lies in the possibility of further application of the essential provisions and conclusions both in psychological and pedagogical activity and in the educational process.
Keywords: Organizational and educational games, motivated audience, motivational opportunities, Russian as a foreign language, grammatical skills, suggestopedia, gaming technologies.